The study of postmortem blood gamma-hydroxybutyric acid (GHB) concentrations in Thai dead bodies unrelated to GHB use - Kumfao N. (2023)
Background: Gamma-hydroxybutyric acid (GHB) is classified as a category I psychotropic substance in Thai legislation. It can be exogenously consumed or endogenously produced and cut-off concentrations are required. Baseline GHB concentration ranges in Thai postmortem cases are still not available. Objectives: To determine baseline GHB concentrations and factors influencing GHB concentrations in Thai postmortem cases. Materials and methods: Postmortem femoral and cardiac blood samples were collected from Thai cadavers aged 18 years old or older sent for medico-legal autopsies at the Department of Forensic Medicine, Siriraj Hospital, Mahidol University between 18th August 2021 and 25th January 2022 with postmortem interval (PMI) not greater than 24 hours. Case data including sex, age, PMI, sites of collection and causes of death were recorded. Blood GHB concentrations were extracted using protein precipitation and analyzed by gas chromatography-mass spectrometry (GC-MS). Descriptive statistics, paired samples Wilcoxon signed-rank test, Spearman's correlation, Mann-Whitney U test and Kruskal-Wallis H test were analyzed where appropriate. Results: A total of 150 subjects were recruited; 63 (42%) were female with mean age 44.59 years old (range 18-75 years old). Femoral and cardiac GHB concentration ranges were <0.5-20.81 µg/mL and 1.12-39.04 µg/mL, respectively while median GHB concentrations in femoral and cardiac blood were 6.38 and 8.41 µg/mL. Femoral GHB concentrations were significantly lower than cardiac GHB concentrations (p<0.001). Both femoral and cardiac blood showed a positive correlation between GHB concentrations and PMI (Spearman’s correlation =0.52 and 0.32, p<0.001). Most GHB concentrations in femoral blood were less than 10 µg/mL and almost all samples from both sources had GHB concentrations less than 30 µg/mL. Conclusion: GHB concentrations in Thai postmortem cases were <0.5-20.81 µg/mL in femoral blood and 1.12-39.04 µg/mL in cardiac blood, respectively. GHB concentrations in femoral blood were significantly lower than in cardiac blood. GHB concentrations significantly increased with longer PMI.